2002
DOI: 10.1038/emm.2002.27
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression profiling of 8-chloroadenosine- and 8-chloro-cAMP-treated human neuroblastoma cells using radioactive human cDNA microarray

Abstract: Previous reports raised question as to whether 8-chloro-cyclic adenosine 3,5-monophosphate (8-ClcAMP) is a prodrug for its metabolite, 8-Cl-adenosine which exerts growth inhibition in a broad spectrum of cancer cells. The present study was carried out to clarify overall cellular affects of 8-Cl-cAMP and 8-Cl-adenosine on SK-N-DZ human neuroblastoma cells by systematically characterizing gene expression using radioactive human cDNA microarray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Numerous studies suggest that 8-Cl-cAMP, a potent analog of cAMP, induces growth inhibition in vitro and in vivo in a broad spectrum of human carcinomas, including neuroblastoma cell lines [23][24][25]29]. Although 8-Cl-cAMP has been used in clinical trials the mechanism of its action remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies suggest that 8-Cl-cAMP, a potent analog of cAMP, induces growth inhibition in vitro and in vivo in a broad spectrum of human carcinomas, including neuroblastoma cell lines [23][24][25]29]. Although 8-Cl-cAMP has been used in clinical trials the mechanism of its action remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 8-Cl-cAMP exerts dual anticancer activity on human SH-SY5Y cells through the inhibition of cell proliferation and the induction of apoptosis [23,24]. A study was carried out in order to clarify the overall cellular effects of 8-Cl-cAMP and 8-Cl-AD on SK-NDZ human neuroblastoma cells in a gene expression study using a cDNA microarray [25]. The obtained results indicated that the two drugs shared common gene expression down-regulation pathways, but used distinct pathways for the up-regulation of different gene clusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the A549 cell line is a human lung carcinoma cell line. Others have reported the presence of mRNA for IL-32 in Epstein-Barr virus infected lymphoma cells, 3 neuroblastoma cells, 4 and haematopoietic progenitor cells. 5 Primary human B cells, even when stimulated with IgM or anti-CD40, do not express significant IL-32.…”
mentioning
confidence: 99%
“…The IL-32 encoding gene locus has been identified at chromosome 16p13.3 and six isoforms, IL-32α, IL-32β, IL-32γ, IL-32δ, IL-32ε, and IL-32ξ, were identified by Kim et al and Chen et al (11,12). Moreover, several studies identified the production of IL-32 in other cell types, including epithelial cells and other monocytes, as well as the presence of IL-32 mRNA in Epstein-Barr virus-infected lymphoma, neuroblastoma, and hematopoietic progenitor cells (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%